Malignant peripheral nerve sheath tumor - a case report and review - Rabelo Gonzalez Veldman, Danielle (2020)
This case report aims to contribute to the understanding and to present a new look on the treatment of a rare, aggressive and poorly understood pathology, known as malignant tumor of the peripheral nerve myelin sheath. The objective of this research is to help building a better understanding of this pathology and to evaluate what is new in diagnosis and treatment. We used PubMed’s articles with the descriptors: malignant peripheral nerve sheath tumor, Ki67, and malignant tumor immunohistochemistry of the peripheral nerve sheath. 17 articles were selected. We also used the descriptor “sarcoma staging” for the visualization of a book chapter and a journal. Malignant neoplasm of the peripheral nerve myelin sheath is a disease that mainly affects neurofibromatosis-1 or patients with prior radiotherapy, but may occur randomly, as with the patient in question. Due to illness multiple incidence locations, the symptoms may be late and staging is difficult. The staging is performed taking into account the size of the primary tumor, its location, lymph node involvement, presence of distant metastases and degree of cell differentiation. The diagnosis is made after resection of the piece with anatomopathological and immunohistochemical analysis, which may delay the treatment. Therefore, it has been seen that the most common treatment continues to be complete surgery with free margins, but there are promising studies in the genetics field for the treatment and better understanding of this pathology